Inhibition of microsomal cortisol production by (–)‐epigallocatechin‐3‐gallate through a redox shift in the endoplasmic reticulum—A potential new target for treating obesity‐related diseases. (29th March 2013) - Szelényi, Péter; Révész, Katalin; Konta, Laura; Tüttõ, Anna; Mandl, József; Kereszturi, Éva; Csala, Miklós
Abstract : Conversion of cortisone to cortisol by 11β‐hydroxysteroid dehydrogenase type 1 (11βHSD1) in the endoplasmic reticulum (ER) of the target cells is a major determinant of glucocorticoid action, and plays an important role in the development of obesity‐related diseases. Inhibition of 11βHSD1 activity is, therefore, considered as a promising novel strategy for the treatment of metabolic syndrome and diabetes. Tea flavanols and their major representative, epigallocatechin gallate are known as antiobesity and antidiabetic agents. Their impacts on blood glucose level, hepatic glucose production, and insulin responsiveness resemble those observed on inhibition or depletion of 11βHSD1. We aimed to study the effect of epigallocatechin gallate on 11βHSD1 activity in ER‐derived rat liver microsomes by measuring cortisone and cortisol with HPLC. Cortisol production was efficiently suppressed in a concentration dependent manner in intact microsomal vesicles. However, this effect was abolished by membrane permeabilization; and the three proteins involved in the overall process (11βHSD1, hexose 6‐phosphate dehydrogenase, and glucose 6‐phosphate transporter) were not or only mildly affected. Further investigation revealed the oxidation of luminal NADPH to NADP +, which attenuates cortisone reduction and favors cortisol oxidation in this compartment. Such a redox shift in the ER lumen might contribute to the beneficial health effects of tea flavanols and should be regarded as a promising strategy for the development of novel selective 11βHSD1 inhibitors to treat obesity‐related diseases. © 2013 BioFactors 39(5):534–541, 2013